FAKTOR-FAKTOR YANG MEMPENGARUHI PERILAKU BELAJAR AKUNTANSI DI DAERAH 3T - Dokman Situmorang; Veneranda Rini Hapsari (JURNAL AKUNTANSI, EKONOMI dan MANAJEMEN BISNIS, 2019)
Based on the preliminary survey, the Bengkayang State Vocational High School 1 Bengkayang currently only has four teachers in the field of Accounting. Whereas the library only has 100 book examplers. In addition there are also computer lab facilities but no one can teach accounting computers. The purpose of this study is to find factors that influence accounting learning behavior. The population in this study were all students. The research sample is as many as 30 students who are in Bengkel 1 Vocational School majoring in accounting. The research method is descriptive and the research design is a qualitative case study. The results of this study are that those who study accounting in this case the students produce an impact that affects behavior both from within and outside themselves when studying accounting, the impact can be negative or positive for their accounting knowledge. The impact is in the form of good behavior that arises from within themselves or behavior that comes from people around them.